Latin America in the Roblox Metaverse: UGC, City branding and Soft Power - Sidorenko Bautista, Pavel (Street Art & Urban Creativity, 2025)
This study explores how Latin American territories leverage the metaverse, particularly the Roblox platform, to enhance their visibility and appeal to Generation Alpha. Through a case study of specific actors and their strategies, this study investigated the virtual marketing efforts employed by these territories. The theoretical framework distinguishes between immersive and semi-immersive metaverse experiences, highlighting the differences between centralized and decentralized virtual environments. The millennial generation, which has the greatest resources to invest in digital assets, is currently the most active user group in the metaverse. However, the engagement of Centennials and Alphas, the digital natives, is becoming increasingly apparent. Despite substantial investment in the metaverse, the lack of interoperability remains a primary technical challenge. This study aims to shed light on how Latin American territories navigate this evolving digital landscape to assert their identity and compete for attention on a global stage.
Keywords: Metaverse; City branding; Place branding; Gen Alpha; Roblox; Latin America; Virtual Marketing; Scopus